Positive Association Between Betatrophin and Diabetic Retinopathy Risk in Type 2 Diabetes Patients - Wang, Y.-Y.; Zhang, D.; Jiang, Z.-Y.; Lu, X.-Q.; Zheng, X.; Yu, Y.-J.; Wang, Y.-G.; Dong, J. (Hormone and Metabolic Research, 2016)
Betatrophin is a recently identified protein that has been shown to be associated with lipid metabolism and insulin resistance. This study aimed to measure serum betatrophin concentrations in patients with type 2 diabetes (T2DM) and evaluate the association of betatrophin with diabetic retinopthy (DR). Serum betatrophin concentrations were compared between (1) gender-, age- and body mass index-matched T2DM patients with (n=17) or without (n=33) DR; (2) gender-, age-, and body mass index-matched healthy subjects (n=31), newly-diagnosed T2DM patients before treatment (n=24), and T2DM patients under antidiabetic treatment (n=35). Serum betatrophin concentrations were determined by the enzyme-linked immunosorbent assay. Multivariate logistic regression was performed to assess the association between betatrophin concentration and DR. Serum betatrophin concentration was significantly associated with DR in T2DM patients under treatment (Odds Ratio 2.01; 95% Confidence Interval 1.12–3.60; p=0.019). Betatrophin concentrations were significantly increased in treated T2DM patients compared to the healthy subjects (4.17±0.60 vs. 0.54±0.07 ng/ml; p<0.001). Serum betatrophin concentrations are increased in T2DM patients under antidiabetic treatment and positively associated with diabetic retinopathy.
Keywords: betatrophin; type 2 diabetes; diabetic retinopathy